PENYULUHAN TENTANG BANTUAN PELAYANAN HUKUM KEPADA MASYARAKAT DENGAN KONTEKS OTONOMI DAERAH DI TANGERANG - Abdur Rahim; Husna Zulbi Aulia; Fatur Padilah; Permata Dewi Kania; Nugraheni Kus Susilaningsih; Al Fathin Ramadhan; Imam Fathan Mubin; Fadillah Mulyadi (LPPM Universitas Bina Bangsa, 2023)
Legal service assistance is a constitutional right of every citizen to guaranteed protection and equality before the law, as a means of recognizing human rights (HAM). This counseling is in collaboration with the Hade Indonesia Raya Legal Aid Institute (LBH) in Tangerang. Getting legal service assistance for everyone is a manifestation of access to justice as an implementation of guarantees of legal protection, and guarantees of equality before the law. Legal service assistance to the community in the context of regional autonomy can assist the community in managing their own household, because in essence regional autonomy is independence to manage and manage their own household. Counseling on legal service assistance aims to provide understanding to the community in Tangerang on the role of the local government in providing legal protection in accordance with the 1945 Constitution. The method of implementation is by providing counseling, followed by questions and answers to obtain results and solutions as a form of solving problems and obstacles encountered, by providing examples of cases that have occurred. The material provided in this service is divided into several aspects so that people can understand it thoroughly. The results of this service show that the understanding of the community in Tangerang in understanding the law regarding the goals of regional autonomy has increased and understanding of supervisory procedures related to community services, especially around Tangerang.